Textual curation : authorship, agency, and technology in Wikipedia and Chambers's Cyclopædia - Kennedy, Krista (Studies in rhetoric/communication., 2016)
A study of the role community, financial support, texts, information structures, interfaces, and technology plays in collaborative works.